Variability in surgical treatment of metastatic colorectal cancer (literature review) - A. Yu. Dobrodeev; D. N. Kostromitsky; S. G. Afanasyev; A. S. Tarasova; N. N. Babyshkina; A. A. Ponomareva (Сибирский онкологический журнал, 2023)
Background. Colorectal cancer (CRC) is one of the most common cancers and one of the most leading causes of cancer-related deaths worldwide. Approximately 35 % of CRC patients have liver metastases at the time of diagnosis. These patients have a poor prognosis, with the 5-year survival rate of 15 %. Given the poor survival with currently approved methods, the development of the optimal treatment options is needed.The purpose of the study was to search for data on the development of surgical techniques for the treatment of patients with metastatic CRC (mCRC) with isolated liver metastasis.Material and Methods. Literature search was carried out in Medline, Cochrane Library, Elibrary and Pubmed databases, including publications characterizing historical and modern results (from 1976 to 2021).Results. Liver resection in mCRC patients with isolated liver metastasis is the only treatment that offers a chance of increasing the 5-year survival rate up to 45–60 %. Radical surgery should include the removal of the primary tumor and all metastases with negative histological resection margins while preserving sufficient functional liver parenchyma. The paper discusses various approaches to surgical treatment of mCRC patients with liver metastases, with an assessment of their advantages and disadvantages, as well as presents data on perioperative and oncological outcomes.Conclusion. The surgical treatment strategy should be adapted for each mCRC patient with synchronous liver metastases. The core function of a multidisciplinary team is to determine the patient’s treatment plan combining surgery and systemic chemotherapy, which will improve the immediate and long-term treatment outcomes.